“… the ruins of Europe in back of me.” Jan Klata’s Shakespeare and the European condition - Cieślak, Magdalena (Studia Anglica Posnaniensia, 2016)
The hybridized and contextualized Shakespeare becomes for Klata a way to comment on current issues that he sees as vital, like dealing with the burden of the past, confronting the reality of the present, or understanding and expressing national identity, problems that are at once universal and specific for a person living in the EU in the twenty first century.